Anti‐Infective Application of Graphene‐Like Silicon Nanosheets via Membrane Destruction. Issue 3 (1st January 2020) - Luo, Yao; Ge, Min; Lin, Han; He, Renke; Yuan, Xiangwei; Yang, Chao; Wang, Wei; Zhang, Xianlong
Abstract: The increasing problem of bacterial resistance to the currently effective antibiotics has resulted in the need for increasingly potent therapeutics to eradicate pathogenic microorganisms. 2D nanomaterials (2D NMs) have unique physical and chemical properties that make them attractive candidates for biomedical applications. Recently, the application of 2D NMs as antibacterial agents has attracted significant attention. Herein, a novel 2D graphene‐like silicon nanosheet (GS NS) antimicrobial agent is fabricated from pristine silicon crystals by ultrasonication, which results in a highly exfoliated planar morphology and a significantly larger surface area as compared with bulk silicon. The GS NSs exhibit remarkable in vitro broad‐spectrum bactericidal activity against Gram (−) Escherichia coli and Gram (+) Staphylococcus aureus because of a close interaction with the bacteria, which leads to highly efficient membrane destruction. The in vivo studies demonstrate that the local administration of GS NSs effectively mitigates implant‐related infection by reducing the bacterial burden of the extracted samples and accelerating the remission of local inflammation. Based on these encouraging results, GS NSs are expected to be a useful new member of the 2D NMs family, with the potential of effectively killing pathogenic bacteria in clinical applications. Abstract : New highly exfoliated 2D graphene‐like silicon nanosheets (GS NSs) with significantly higher surface area are fabricated from pristine silicon crystals via ultrasonication. The GS NSs exhibit excellent dose‐dependent anti‐infective efficacy through a direct bacteria–nanomaterial contact, an intimate membrane‐disruptive interaction, and the disruption of vital bacterial membrane or component in vitro and in vivo.